Assessing the stability of historical and desiccated snake venoms from a medically important Ecuadorian collection - de Almeida, José R. (2020)
Bothrops asper and Bothrops atrox are important venomous snakes from Ecuador responsible for the most of ophidic accidents, which in the past were treated with a national polyvant antivenom. For years, the venom pools were collected and stored at room temperature in a laboratory. Taking into account the controversial ability of desiccated samples to retain their biological effects and enzymatic activities, we investigated the biochemical and toxicological properties of venoms after years of storage. The proteomic profiles of historical venoms analyzed by high-performance liquid chromatography and electrophoresis are very similar. The fresh batches of venom were more lethal than those stored for years, just as the initial and current LD50 values of these samples changed. Significant differences were showed in the myotoxic and hemorrhagic activity of some venom pools, while no significant statistical differences were found for the edema activity. The enzymatic assays revealed a variation in proteolytic activity on azocasein and phospholipase A2 activity, and low differences were reported for thrombin-like serine protease activity. The maintenance of the proteomic profile and certain toxicological activities convert this venom library in a valuable source for research purposes. Nonetheless, the significative reduction of toxicological activities, such as hemorrhagic activity not feasible using these samples for the antivenom production.